Tracheal Compression by Aberrant Innominate Artery: A Case Report - Ankit Agarwal; Nidhi Bedi; Pankaj Abrol; Ankit Parakh; Renu Sharma (Journal of Clinical and Diagnostic Research)
The brachiocephalic trunk arises from the convexity of the aortic arch, posterior to the manubrium sterni. In rare cases, the origin of the brachiocephalic trunk is shifted to the left of the midline, crosses the trachea through an oblique course, and rises upwards. Sometimes this aberrant artery due to an anomalous course can cause a triad of symptoms consisting of cough, stridor, and occasional apnoea known as innominate artery compression syndrome. Here one such case is presented in which, a nine-month-old infant presented with complaints of recurrent cough and noisy breathing since 10 days of age. The infant had a history of frequent hospital admissions for cough since one month of age where he was given nebulisation but with only partial response. A bronchoscopy was done which was suggestive of mid-tracheal compression. Contrast-Enhanced Computed Tomography (CECT) chest confirmed the diagnosis and the child was then referred to a cardiac surgeon for further management. It is important to note that compression of the trachea or tracheobronchial tree by congenital vascular anomalies is not an uncommon cause of stridor and should always be considered a differential diagnosis while evaluating such cases.